Massive Hydrothorax and Ascites as the Primary Manifestation of Infection With Clostridium difficile: A Case Report and Literature Review - Liang, Yujian; He, Xiufang; Wang, Ti; Chen, Yili; Huang, Huimin; Tang, Wen; Li, Yijuan (Frontiers in Pediatrics, 2020)
Introduction:Clostridium difficile infection (cdi) often occurs with long-term and irregular use of antibiotics. Patients with tumors receiving both antibiotics and chemotherapy are at a high risk of cdi. The symptoms of cdi vary but can include diarrhea, hypovolemia, electrolyte imbalance, hypoproteinemia, toxic megacolon, gastrointestinal tract perforation, disseminated intravascular coagulation, sepsis, and other lethal complications. Here, we report a rare clinical manifestation associated with cdi in a child with lymphoma presenting with massive hydrothorax and ascites. Case Presentation: A 6-year-old girl who was on chemotherapy for lymphoma presented with fever and was treated with intravenous broad-spectrum antibiotics 3 days before admission to our hospital. On the day before admission, she developed abdominal distension and diarrhea. After admission, broad-spectrum antibiotic therapy was initiated, and her hydrothorax and ascites were drained. An initial extensive microbiological evaluation revealed no pathogens, and laboratory tests and imaging studies of the pleural and peritoneal effusions revealed no evidence of cancer. The initial culture results for C. difficile were negative. The patient was diagnosed with CDI only after a positive test result for C. difficile toxin B gene and a repeated stool culture test revealed CDI. Intravenous antibiotics were suspended and replaced with oral vancomycin and Saccharomyces boulardii, which resulted in successful treatment and a good post-discharge outcome. Conclusions: Massive hydrothorax and ascites are rare manifestations associated with CDI. CDI can occur in individuals with risk factors such as those undergoing broad-spectrum antibiotic therapy.